In memoriam of prof. Zigmas Žemaitis (1884–1969) - Henrikas Jasiūnas (Lietuvos Matematikos Rinkinys)
In this paper we present a review of the social, political, scientific, and pedagogical activities of a prominent figure of the Lithuanian social scene.